Identification of novel QTL associated with whitebacked planthopper (WBPH) and brown planthopper (BPH) resistance in the rice line RP2068 - Sahu, Nihar; Naik, Sabhavat Bhaskar; Padmavathi, G.; Gangurde, Sunil S.; Pandey, Manish K.; Bentur, Jagadish Sanmallappa; Divya, Dhanasekar (Elsevier, 2025)
This study aimed to identify QTL governing three traits of the resistance against the two planthoppers such as damage score (DS), nymphal survival (NS) and days to wilt (DW) using the 94 RIL population derived from the cross TN1/RP2068 utilizing 125 SSR and 1500 SNP markers. In case of the whitebacked planthopper (WBPH) five major and three minor QTL while for the brown planthopper (BPH) four major and seven minor QTL were identified to be associated with these three traits. Two major QTL, each on chromosomes 1 and 2, were responsible for DS and NS against WBPH accounted for 25% and 16% of the phenotypic variance (PVE). In addition, two QTL on chromosome 6 accounted for 17% (DS), 16% (NS) and one QTL on chromosome 8 accounted for 18% of the PVE for NS, respectively. As no QTL has been reported so far on chromosome 1 flanked by Fbox and RBO markers associated with WBPH resistance, we designed this locus as the novel QTL-WBPH20(t). Against BPH, in addition, to the already reported BPH33(t) gene, two new QTL were identified on chromosomes 1 and 4 accounted for 21% &, 17%, and 37% &, 16% PVE for DS and NS, respectively. Significantly, a single locus on chromosome 1 flanked by RM1247 and SNP1715514 was found to be associated with both the planthoppers resistance. Based on in silico analysis and RNA sequencing data (published earlier), 21 putative candidate genes for WBPH and four for BPH were identified within these major QTL regions.